A history of Selangor, 1766-1939 - Gullick, J.M (Monographs of the Malaysian Branch, Royal Asiatic Society, 1998)
John Gullick in his important new A History of Selangor (1766-1939) builds on his previous research and writing, with particular emphasis on how the immigrant community developed agriculture in Selangor and made it their home, and takes the story up to 1939.